Computational Analysis to Design Loudspeakers with Nonconventional Forms (2021)
This word presents the study of the frequency response between two loudspeaker configurations, where the first is a conventional circular form and the second a nonconventional form with modification over its geometry. This analysis was done using the FEM computational ANSYS® software. This goal surged from the necessity to research how to improve the esthetic and electro- acoustical properties of a loudspeaker while the geometry of its diaphragm is modified and to get a new nonconventional loudspeaker models for the industry. A hendecagon loudspeaker model was simulated and compared to a conventional circular loudspeaker. The results presented were the modal analysis, harmonic response and frequency response.